An Integrated Methodology of Rough Set Theory and Grey System for Extracting Decision Rules - Hossam Mohamed; Mahdy S. El-Paoumy (Institute of Advanced Engineering and Science, 2013)
Grey system theory and rough set theory are two different mathematical tools that are used to deal with uncertain or incomplete information, and yet they are relevant and complementary to a certain degree. The appropriate hybrid of the two theories can overcome the shortages of their definitions and applications and thus has more powerful functions. This paper proposes An Integrated Methodology that extracting decision rules based on combining grey system and rough set theory. The effectiveness of the proposed methodology was verified by application of this methodology to discover grade rules of electrical transformer evaluation.